Розробка пневматичної системи керування на основі електропневматичного перетворювача з пропорційним електрокеруванням - Крутіков, Геннадій Анатолійович; Стрижак, Мар'яна Георгіївна (НТУ "ХПІ", 2012)
Була здійснена заміна дискретної системи керування шліфувально-обдирочної машини на точну аналогову систему керування, що грунтується на використанні електропневмтичного перетворювача – пневматичного редукційного клапана з пропорційним електрокеруванням. Це дозволило розширити діапазон надійної роботи і тримати струм електромотора в оптимальному режимі. Replacement was made discrete control system grinding and deburring machines precise analog control system based on the use of electro-pneumatic converter - pneumatic pressure reducing valve with proportional electric control. It is possible to expand the range of safe operation and to keep current motor optimally.

Provides information on the impact of design features of equipment for thermochemical and thermal-pulse processing complex-area detail on the application of advanced technologies, as well as a classification of materials, the relative energy intensity of production processes, depending on the opti-mum treatment time and temperature on the thickness of the elements and the elimination of parts. An algorithm is also facilities for termal-pulse process that implements the safe operation and automatic selection modes.
Keywords: системи керування; електропневматичні перетворювачі; пневматичні системи; пневмоприводи; pneumatic actuator; mathematical model; nondimensional parameters